109 Overexpression of endothelial insulin-like growth factor-1 receptors (IGF-1R): a novel role for IGF-1R in endothelial function and repair. (16th May 2012) - Imrie, H; Viswambharan, H; Sukumar, P; Abbas, A; Yuldasheva, N; Gage, M; Galloway, S; Wheatcroft, S B; Kearney, M T
Abstract : Introduction: Endothelium-derived nitric oxide (NO) is a critical regulator of vascular homeostasis, repair and regeneration. We recently demonstrated that reducing insulin-like growth factor-1 receptor (IGF-1R) numbers in the endothelium, thereby decreasing the proportion of insulin resistant hybrid receptors, enhances NO bioavailability and increases endothelial cell (EC) insulin sensitivity (Abbas*, Imrie*, Viswambharan* et al. Diabetes 2011;60 :2169–78). Methods: To examine the effect of increasing IGF-1R in EC we generated transgenic mice overexpressing the human IGF-1R in EC (human IGF-1R endothelium overexpressing mice (hIGFREO)). Glucose and insulin sensitivity were measured by tolerance testing and plasma insulin and IGF-1 levels were analysed by ELISA. The response of aortic rings to increasing doses of phenylepherine (PE), with and without L-NMMA (a NO inhibitor), were measured ex vivo in an organ bath. NO release, eNOS activity and phosphorylation of eNOS (all in response to insulin) were measured by DAF fluorescence, the conversion of L-arginine to L-citrulline, and western blotting respectively. Endothelial regeneration was investigated by guide-wire injury of the femoral artery with quantification of Evans-blue dyed denuded area and migration assays were performed in response to VEGF by H&E staining. Results: Increased endothelial IGF-1R numbers had no effect on glucose tolerance or insulin sensitivity in hIGFREO mice compared to wild-type (wt) littermates and fasting plasma glucose, insulin and IGF-1 levels were similar. Aortae from hIGFREO mice were hypercontractile to phenylephrine (PE) (Emax wt =0.62±0.045 vs hIGFREO =0.91±0.045, p=0.036) and had blunted constrictor responses to LNMMA (Emax wt =106.1±30.10 vs hIGFREO =47.7±9.87, p=0.048) indicating reduced basal NO bioavailability. In response to insulin EC from hIGFREO had: reduced NO release (wt =4500±1000 vs hIGFREO =1500±700, p<0.05); reduced eNOS activation (wt =170%±25 vs hIGFREO 58%±3, p<0.04); and decreased phosphorylation of eNOS (p=0.027). After endothelium denuding arterial injury hIGFREO mice demonstrated accelerated endothelium regeneration (recovered area: wt =40.27%±5.7 vs hIGFREO =57.25%±2.3, p=0.003) and enhanced endothelial cell migration under control conditions and in response to VEGF (p<0.001). Conclusions: Manipulation of IGF1-receptor numbers may represent a novel strategy for altering insulin sensitivity and vascular NO production. This data demonstrates uncoupling of endothelial NO bioavailability and vascular repair.